2000
DOI: 10.1093/humrep/15.7.1440
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of LH during ovarian stimulation: effects differ in cycles stimulated with purified urinary FSH and recombinant FSH

Abstract: There has been much debate about the role of luteinizing hormone (LH) during follicle stimulating hormone (FSH)-treated ovarian stimulation for assisted reproduction, where the endogenous LH is suppressed using a gonadotrophin-releasing hormone analogue. The requirement for LH in oestradiol biosynthesis is established, but other effects of 'insufficiency' are less clear, and little attention has been paid to the specific origin of the FSH used. The aim of this study was to examine the roles of profoundly suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…If these patients were to proceed to assisted conception treatment, poor ovarian performance and low E 2 production would be expected unless exogenous LH is added during stimulation. It has been suggested that adding exogenous LH to such patients would improve ovarian response and optimize steroidogenesis (20,21). It may be worth considering in such patients to proceed with daily buserelin instead of exogenous LH, which may increase the endogenously secreted LH levels, as shown in this study.…”
mentioning
confidence: 77%
“…If these patients were to proceed to assisted conception treatment, poor ovarian performance and low E 2 production would be expected unless exogenous LH is added during stimulation. It has been suggested that adding exogenous LH to such patients would improve ovarian response and optimize steroidogenesis (20,21). It may be worth considering in such patients to proceed with daily buserelin instead of exogenous LH, which may increase the endogenously secreted LH levels, as shown in this study.…”
mentioning
confidence: 77%
“…On the other hand, other studies have shown that a low concentration of endogenous LH (<3 mIU/ml) in the late follicular phase is associated with lower fertilization rates and higher biochemical pregnancy rates. It has been suggested that when using recombinant FSH only, it may be of clinical benefit to add LH in the late follicular phase or to further reduce the dose of GnRH analogue [33][34][35][36]. Conversely, it has been reported that patients with very suppressed LH levels respond similarly to those moderately suppressed, and only 6% of patients would benefit from exogenous LH administration [32].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, evidence indicates that a subset of women has less responsive ovaries to COS explained by a variety of factors, including reduced paracrine ovarian activity [153], LH receptor polymorphisms [152], reduced androgen secretory capacity [154], decreased number of functional LH receptors [155], and reduced LH bioactivity while LH imnunoreactivity is unchanged [156,157]. Thus, it has been hypothesized that the aforementioned women would benefit from the use of LH-containing gonadotropin preparations [144,146,150,158,159].…”
Section: Rationale Of Lh Supplementation: To Whom and Why?mentioning
confidence: 99%